2019
DOI: 10.1186/s12957-019-1731-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in peritoneal surface malignancies: evidence from a Czech nationwide population-based study

Abstract: BackgroundThe aim of this study is to identify the incidence trends of primary and secondary peritoneal surface malignancies in a representative Czech population.MethodsData were obtained from patients registered in the Czech National Cancer Registry between 1979 and 2016. The incidence rates were analyzed between 2012 and 2016. To observe the incidence trends, we analyzed the data from two time periods, 1979–2005 and 2006–2016. The analyzed data included age, sex, and the histological types and primary origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Peritoneal metastasis is one of the most common forms of metastasis in patients with gastric cancer reported in the literature between 10 and 20% [ 3 , 4 , 19 ]. Therefore, an accurate diagnosis remains crucial for prognostic evaluations and therapeutic decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal metastasis is one of the most common forms of metastasis in patients with gastric cancer reported in the literature between 10 and 20% [ 3 , 4 , 19 ]. Therefore, an accurate diagnosis remains crucial for prognostic evaluations and therapeutic decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal carcinomatoses are a heterogeneous group of disease which can either arise primarily from the peritoneum itself or metastasis of other tumors in the abdomen located at the colon, rectum, appendix, stomach or ovary ( 1 ). Indeed, the treatment plan varies with the disease histology and the extent of peritoneal involvement; but if left untreated, survival with this disease can be as low as 4 months ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the poor prognosis of patients with ovarian metastases, some authors of reports published before 2000 proposed only palliative surgical resection, especially when extensive intra-abdominal disease or distant metastasis is present [ 4 6 ]. However, a recent study revealed a better prognosis after complete ovarian metastasis resection or cytoreductive surgery [ 7 17 ]. In our series, the 5-year overall survival rate of patients treated by R0 resection was 68.6%, versus 0% in those who underwent R1/2 resection.…”
Section: Discussionmentioning
confidence: 99%